2005
DOI: 10.1002/dvdy.20455
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene required for de novo DNA methylation of the zebrafish no tail gene

Abstract: The zebrafish no tail gene (ntl) is indispensable for tail and notochord development. We have shown previously that ntl is de novo methylated during early embryogenesis. To find the gene that de novo methylates ntl and understand the meaning of this methylation, we cloned seven genes that encode the conserved catalytic domain of methyltransferases. We found that injection of antisense morpholino oligonucleotides against one of them, termed dnmt7, into eggs significantly reduced the level of ntl methylation, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…In addition, zebra fish harbor orthologs of each of the mammalian DNA methyltransferases, including the founding member, DNMT1 (28,30,43). By convention, we present zebra fish genes in lowercase and human genes in uppercase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, zebra fish harbor orthologs of each of the mammalian DNA methyltransferases, including the founding member, DNMT1 (28,30,43). By convention, we present zebra fish genes in lowercase and human genes in uppercase.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, our findings might predict that DNA methyltransferases other than Dnmt1 may be required for terminal differentiation of those organs which remain unaffected by Dnmt1 and Suv39h1 knockdown. Indeed, zebra fish bear additional DNA and histone methyltransferases that are conserved in all vertebrates, raising the possibility that additional enzymes may likewise direct tissue-specific differentiation (43). In support of this, recent evidence indicates that methylation of a developmentally regulated gene (ntl) in zebra fish depends selectively upon Dnmt7 (43).…”
Section: Discussionmentioning
confidence: 99%
“…A homology search revealed that 6 of the zebrafish DNMTs exhibit a high degree of similarity to DNMT3A/B, termed Dnmt3-8 (Shimoda et al, 2005). Interestingly, knockdown experiments suggested that Dnmt7 was responsible for de novo methylation of ntl but not other forms of de novo methylation, such as at transgenes (Shimoda et al, 2005).…”
Section: Zebrafish -Danio Reriomentioning
confidence: 99%
“…Interestingly, knockdown experiments suggested that Dnmt7 was responsible for de novo methylation of ntl but not other forms of de novo methylation, such as at transgenes (Shimoda et al, 2005). The homologues most similar to Dnmt3A are Dnmt6 and Dnmt8, and it is of note that Dnmt3A is expressed as 2 major isoforms in mammals.…”
Section: Zebrafish -Danio Reriomentioning
confidence: 99%
“…These are subdivided into maintenance (Dnmt1) and de novo (Dnmt3a and Dnmt3b) methyltransferases. Dnmt2 is also present, but recombinant studies and inactivation of Dnmt2 in embryonic stem cells indicate that it possesses no methyltransferase activity (Shimoda et al 2005), though it possibly functions in methylation of RNA (Goll et al 2006). The de novo Dnmts, Dnmt3a and Dnmt3b, are responsible for establishing the initial CpG methylation pattern while Dnmt1 maintains this pattern during cell division and repair.…”
Section: Dna Methylationmentioning
confidence: 99%